ประชาสังคม เวทีสาธารณะ กับกระบวนการกลายเป็นประเด็นสาธารณะ : ศึกษากรณีโครงการก่อสร้างโรงบำบัดน้ำเสียคลองด่าน จังหวัดสมุทรปราการ - วิรัชต์ แสงดาวฉาย (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
The objectives of this study are to review the role of civil society in Thai society in the establishment and its existence. The conditions and channel which civil society can play a role in the public sphere in political society. Through these conditions and channels people and civil groups can play their roles towards public issue management. The study was carried out through public-issue peocesses in the case of the Klong Dan Wastewater Treatment Plant Construction Project at Samut Prakarn Province. The study identifies the issue of case environmental management focusing on people’s participation in public management of large infrastructure project and the role of civil groups. The findings show that public-issue peocesses of the project are the concern of people at individual, local and national levels. There are processes with multi-functions and various dimensions. Lack of poltical information on legal facts accererlated social movement against the project rationalliy. Public conscience of the social groups in specific political arena at defferent levels provide an opportunity for people to participate in social movements according to there roles. "The sense of ownership" resulted from the following conditions : sense of belonging to the community, land use benefit, impacts on their living conditions, and project corrution. Moreover, the study pointout the relationship between civil society roles, the setting up of social groups in specific political arena and social movement.